Determinant factors of hospital service quality and patient satisfaction: Hospital logistics management approach - Alfarizi, Muhammad; Ngatindriatun (Asian Management and Business Review, 2022)
This study aims to examine the effect of private hospital logistics factors on treatment satisfaction and specialist patient satisfaction. This study has five construction dimensions of hospital logistics, namely physical accessibility, waiting time, consultation time, hospital hotel services, and administrative procedures. Quantitative explanatory studies with 297 sample size were carried out to achieve the research objectives by examining the relationship between the independent and dependent variables through online data collection questionnaires, tabulations and hypothesis analysis with SEM PLS analysis tools. This study shows significant results for all hypotheses which imply the importance of optimizing hospital logistics performance, especially in terms of the five constructs in improving service quality and patient satisfaction. Optimizing hospital logistics elements in private hospital specialist patient care is a challenge that is not easy because it requires strategic planning and proper resource management. The role of various parties, especially hospital managers and Indonesian health system policy makers, in paying attention to the operational flow of hospital logistics, especially private hospitals, in order to strengthen the private hospital service system in providing health services while running the hospital business.